NIMG-108. PHYSICAL STRESSES IN BRAIN TUMORS. (14th November 2022) - Nia, Hadi; Kumar, Ashwin; Datta, Meenal; Siri, Saeed; McHugh, Jeffrey; Ferraro, Gino; Chatterjee, Sampurna; Rapalino, Otto; Choi, Bryan; Nahed, Brian; Jain, Rakesh
Abstract: Solid stress, distinct from fluid pressure, is a physical force contained in and transmitted by solid components of the brain tumor, including cells and the matrix they produce. Solid stress has been shown to promote tumor progression, and decrease anticancer therapy efficacy. This is especially relevant in brain tumors, as the rigid skull results in these trapped forces, increasing intracranial pressure, and potentially leading to other complications, including neuronal cell death. Here we present a novel method of quantifying these physical stresses in situ in both mice (glioblastoma [U87], brain metastasis [BT474], and ependymoma models) and patients. Briefly, following a craniotomy, mechanical forces that include solid stress are released, which causes the tissue to deform in peaks (areas under compression) and valleys (areas originally under tension). This tissue deformation is imaged via high-resolution ultrasound and analysed via custom MATLAB code to produce an accurate 3D model of the entire mouse brain, including the tumour region. For human samples, a pre-operative MRI is used to generate a detailed 3D model of the human brain. During surgery, the trapped physical stresses results in a bulge of the dura post craniotomy. We use BrainLab to measure the craniotomy induced brain deformation, which is then registered to the pre-operation MRI before being analysed in an identical fashion to the murine models using SolidWorks and Abaqus. We further show that in the brain metastases model, chemotherapy reduces compression stresses by 51%. Further, our technique results in fast processing time (~ 15 minutes), and has the potential to prevent the need for intraoperative MRI based on position simulations. As such, solid stress measurements provide a new class of mechanical biomarkers that can be correlated to clinical outcomes for predictive and prognostic value.